Ga. Code §4413 (1861) - (:unkn) unknown (General Publisher, 1861)
Prohibited conceal carry of any pistol, dirk, sword-cane, spear, Bowie-knife, or any other kids of knives manufactured for offense or defense. Violators guilty of a misdemeanor
--
Keywords: CARRY - CONCEALED